Global Health Governance and Commercialisation of Public Health in India
1 online resource (168 pages)
Keywords: Global health governance has been the subject of wide scholarship, more recently brought to the fore by priorities for global health defined by the Sustainable Development Agenda. The health landscape itself has changed dramatically in the last two decades, shaped by cross-border flows of capital, ideas, technology intermediated through the complex interaction between global, national and local actors and institutions. This book analyses the complex terrain of global health governance and local responses to new global forms of integration and fragmentation in India. It unpacks, both conceptually and empirically, local manifestation and translation of global health architecture and regimes and how these processes influence public health policy and practice; as well as to what extent rules and flows are complied with, resisted and transformed at national and sub-national levels. Drawing together critical scholarship on interactions between global and local actors, focusing on processes, dilemmas, conflicts and trade-offs that such engagement presents for national health policies and health systems, it speaks to this interface between the global, national and local. Filling an important gap in global health governance scholarship in India, the book is a useful contribution to the fields of global health policy, international health and development, health systems, health inequalities, public health, public administration, development studies, social work, nursing, management studies and mainstream social science disciplines that engage with globalisation and health.